High-risk adverse events in two types of single inhaler triple-therapy: a pharmacovigilance study based on the FAERS database - Ruan, Zhishen; Wang, Chunbin; Yuan, Shasha; Fan, Yiling; Xu, Bo; Cong, Xiaodong; Li, Dan; Miao, Qing (Frontiers in Pharmacology, 2025)
ObjectiveSingle inhaler triple therapy is widely used in Chronic Obstructive Pulmonary Disease (COPD) and asthma. This research aimed to analyze adverse events (AEs) associated with Budesonide/Glycopyrronium/Formoterol Fumarate (BUD/GLY/FOR) and Fluticasone Furoate/Umeclidinium/Vilanterol (FF/UMEC/VI).MethodsThis is a cross-sectional study. BUD/GLY/FOR (2020Q3-2024Q3) and FF/UMEC/VI (2018Q1-2024Q3) report files were downloaded from the U.S. Food and Drug Administration’s (FDA) Adverse Event Reporting System (FAERS) database. We use reporting odds ratio (ROR), proportional reporting ratio (PRR), and Bayesian confidence propagation neural network (BCPNN) for disproportionality analysis. The aim was to explore associations between drugs and preferred term (PT) and system organ classification (SOC) levels. We focused on exploring the top 10 PTs of each drug’s BCPNN (IC) effect value and the PT of pneumonia.Results16,355 AEs in BUD/GLY/FOR and 39,110 AEs in FF/UMEC/VI were extracted. Device use issues, oropharyngeal and vocal problems, pneumonia, candida infections, and urinary retention were the standard PTs present in drug leaflets. The risk of device use issues was higher in BUD/GLY/FOR, whereas the risk of pneumonia and candida infection in FF/UMEC/ VI had higher risk. Outside of the drug leaflets, both drugs were associated with a higher risk of AEs in vascular disorders. BUD/GLY/FOR group had a higher risk of AEs in body height decreased and hypoacusis. Notably, this study found an association between the above PTs and drugs, and the causal relationship needs to be verified by further longitudinal studies.ConclusionOur study provides a preliminary exploration of the safety of clinical use of BUD/GLY/FOR and FF/UMEC/VI, and clinicians should be alert to potential adverse effects.